CHOICE OF DRAINAGE LIGATURE IN THE TREATMENT OF COMPLEX FORMS OF ACUTE PARAPROCTITIS - Karabaev J.A. (Research Focus International Scientific Journal, 2024)
Anal abscess is the most popular case in urgent coloproctology. The problem of anal fistula formation remains open. Primary fistulotomy for anal abscess reduces the incidence of fistulas, however, this method of treatment affects the muscle fibers of the obturator apparatus of the rectum and lead to anal incontinence. The role of a loose set-on in the treatment of fistulas is widely known and well-studied, which cannot be said about the use of this method in the treatment of anal abscess. Aim of the study. To research the effectiveness of a loose seton in a two-stage treatment with paraproctitis. Materials and methods. This retrospective study included 60 patients with acute ischiorectal abscess. The patients were divided into 2 groups, 30 persons each. At the first stage of treatment, patients of group A underwent incision and drainage of the abscess, patients from group B, incision and drainage of the abscess was supplemented with a drainage ligature passing through the affected crypt. At the second stage, 22 patients from group A and 30 patients from group B underwent a combined LIFT operation with laser destruction of the fistulous tract. Before the second stage of treatment, patients of both groups underwent transrectal ultrasound in order to exclude the presence of leaks and cavities. The function of anal sphincter was assessed using sphincterometry and a Wexner scale questionnaire before and after the second stage of treatment. Results. The average follow-up period for the patients after the second stage of treatment was 18.3 months. in group A and 16 months in group B. The recurrence in group A were registered in 5 out of 22 people (22.7%), in the group of patients with a loose set-on – in 3 out of 30 persons (10%). Dysfunctions of anal sphincter after the first and second stages of surgical treatment were not registered in any of the groups. Conclusions. The use of loose set-on in two-stage treatment of paraproctitis allows to confidently control draining of abscess, form a consolidated fistulous tract without spurs and leaks, prepare the patient for the second stage of surgical treatment and reduce the recurrence rate after minimally invasive treatment of rectal fistulas without loss of anal sphincter function.